2021
DOI: 10.3390/foods10030637
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Zn2+ Ions Governs the Microbial Quality of Donor Human Milk

Abstract: Donor human milk (HM) obtained at HM banks is exceptionally crucial for the feeding and treatment of preterm infants. Bacterial contaminations of HM in various stages of its handling are very common and can lead to disqualification of donations or severe infections in worse cases. Hence, HM donations are subject to strict bacteriological evaluations pre- and post-pasteurization. The main contaminating species vary between countries, banks and donors and even exhibit inter-individual variation. We initiated an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…This result demonstrates that the release of Zn 2+ by the ZIF‐8 decomposition can be advantageous for antibacterial activity; when Zn 2+ release of ZIF‐8 is induced by acid layer, the released ions can act as an effective antibacterial agent even ZIF‐8 is incorporated in a fibrous structure. Zn 2+ infiltrates the cell membrane of bacteria, intensifying the destruction of the membrane integrity and interfering the enzyme system of bacteria, [ 41,42 ] and this antibacterial action can ultimately inhibit the proliferation of bacteria and resist bacterial infection at the wound site, as the previous study confirmed. [ 43 ] In fact, as the microbial species isolated from infected wounds involves Gram positive bacteria also, additional assay against various bacteria may be needed for the range of practical applications.…”
Section: Resultsmentioning
confidence: 87%
“…This result demonstrates that the release of Zn 2+ by the ZIF‐8 decomposition can be advantageous for antibacterial activity; when Zn 2+ release of ZIF‐8 is induced by acid layer, the released ions can act as an effective antibacterial agent even ZIF‐8 is incorporated in a fibrous structure. Zn 2+ infiltrates the cell membrane of bacteria, intensifying the destruction of the membrane integrity and interfering the enzyme system of bacteria, [ 41,42 ] and this antibacterial action can ultimately inhibit the proliferation of bacteria and resist bacterial infection at the wound site, as the previous study confirmed. [ 43 ] In fact, as the microbial species isolated from infected wounds involves Gram positive bacteria also, additional assay against various bacteria may be needed for the range of practical applications.…”
Section: Resultsmentioning
confidence: 87%
“…Two of these involve: (i) the production of free Zn 2+ ions from the Zn nanoparticles and (ii) the attachment of ZnO nanoparticles to the external part of the bacteria via electrostatic forces [50]. As an element, zinc has been found to be an important factor in multiple vital intracellular processes occurring in all organisms; however, an increase in its concentration could have a detrimental impact for cells [51]. Particularly in bacterial cells, it has been reported that rising levels of free zinc can result in protein deactivation, disruption in glycolysis, polysaccharide synthesis, acid tolerance and proton translocation [52].…”
Section: Discussionmentioning
confidence: 99%
“…[82] Zn 2 + has antibacterial activities against Gram-positive (S. epidermidis, Bacillus cereus) and Gram-negative (E. coli) bacteria. [83] Like Cu 2 + , Zn 2+ ions induce the production of H 2 O 2 , OH À , O 2 À and * OH, generating bacterial membrane damage by ROS-mediated oxidative stress. [84] Zn 2 + also achieves antimicrobial effects through direct enzyme inhibition: in viruses (coronavirus, arterivirus) Zn 2 + inhibits RNA polymerase; in Gram-positive bacteria, Zn 2 + inflicts cell wall destruction via inhibition of transglycolase and transpeptidase enzymes.…”
Section: Metalsmentioning
confidence: 99%
“…Zn 2+ is likewise a broad‐spectrum EAIM [82] . Zn 2+ has antibacterial activities against Gram‐positive ( S. epidermidis , Bacillus cereus ) and Gram‐negative ( E. coli ) bacteria [83] . Like Cu 2+ , Zn 2+ ions induce the production of H 2 O 2 , OH − , O 2 − and ⋅OH, generating bacterial membrane damage by ROS‐mediated oxidative stress [84] .…”
Section: Six Molecular Classes Of Eaimsmentioning
confidence: 99%